Mortality trends in people with disabilities before and during the COVID-19 pandemic in South Korea, 2017–2022 - Kim, Ye-Soon; Kim, Ju-Hee; Kwon, Sooyoung; Kim, Joo-Hee; Kim, Hyun-Ji; Ho, Seung Hee (Frontiers in Public Health, 2024)
Objective: To investigate temporal trends in mortality rates and underlying causes of death in persons with disabilities before and during the coronavirus disease 2019 (COVID-19) pandemic. Methods: Annual mortality rates and causes of death were analyzed using data covering the 2017-2022 period.The mortality rate among people with disabilities increased from 2017 to 2022; the rate was five times higher during COVID-19 in this population than in the general population. When analyzing the cause of death, the incidence of infectious diseases and tuberculosis decreased after COVID-19. In contrast, the incidence of other bacillary disorders (A30-A49) increased. The incidence of respiratory system diseases (J00-J99), influenza and pneumonia (J09-J18), and other acute lower respiratory infections (J20-J22) decreased before COVID-19, while the incidence of lung diseases due to external agents (J60-J70), other respiratory diseases principally affecting the interstitium (J80-J84), and other diseases of the pleura (J90-J94) increased during the pandemic. The risk of COVID-19 death among people with disabilities was 1.1-fold higher for female patients (95% CI=1.06-1.142), 1.41-fold for patients aged 70 years and older (95% CI=1.09-1.82), and 1.24-fold higher for people with severe disabilities (95% CI=1. 19-1.28). Conclusions: The mortality rate in people with disabilities significantly increased during COVID-19, compared with that before the pandemic. People with disabilities had a higher mortality rate during COVID-19 compared with the general population. Risk factors must be reduced to prevent high mortality rates in this population.